Evaluasi Praktik Pengalaman Lapangan Terhadap Dampak Penyelesaian Skripsi Mahasiswa IAIN Curup - Beni Azwar; Wandi Syahindra; Rini Widyastuti (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
The research is behind the issue of policy change implementation of field experience practice of faculty Tarbiyah from 2 months to 4 months with the reason first, the student is less gaining knowledge and experience, secondly, the time of doing PPL on In January to March to coincide with the national exam, third, relating to the allocation of honors for teacher teachers that were calculated according to the number of students he was tutored, and fourth, with the change of the policy of PPL 4 months that effect on Completion of student thesis. The purpose of the research is to know the perception of the stake holder against PPL IAIN Curup and to know a formulation of PPL majors Tarbiyah IAIN Curup. The research method used is qualitative research using an analysis-descriptive approach.  This study saw the implementation of PPL faculty Tarbiyah because the policy changes from 2 months to 4 months. The results showed the school's perception of PPL for paedagogic competence is still lacking, especially in classroom management, RPP manufacturing, and the development of learning evaluation tools. For personal competence is still low on student discipline and managing emotions, while for social competence most students impress their exclusive neighbors.